A rat model of early sepsis: relationships between gentamicin pharmacokinetics and systemic and renal effects of bacterial lipopolysaccharide combined with interleukin-2 - Studena, Sarka; Martinkova, Jirina; Slizova, Dasa; Krs, Otakar; Senkerik, Marian; Springer, Drahomira; Chládek, Jaroslav (Biological & pharmaceutical bulletin, 2012)
A rat model of early sepsis induced by lipopolysaccharide (LPS) combined with interleukin-2 (IL-2) was developed. The primary aim was to assess the pharmacokinetics of gentamicin and sepsis-induced pathophysiological changes. Moreover, the effects on the glomerular filtration rate and tubular function were studied in septic and control rats. First, an intravenous (i.v.) bolus of LPSIL-2 (1 mg/kg-Pseudomonas aeruginosa, 15 µg/kg IL-2) or saline (controls, C) was administred. The Wistar rats were treated 30 min after LPSIL-2 with gentamicin as a 3 mg/kg i.v. bolus followed 10 min later by an i.v. 170-min infusion (GE, 0.09 mg/kg·min(-1)). The monitoring of vital functions, biochemistry and GE concentrations was performed. Creatinine clearance was 2-3 times lower and fractional urea excretion was 3-4 times less in septic rats as compared to controls(p<0.05), although urine flow was comparable. Capillary leakage caused a 55% elevation in the volume of distribution (V(c)) in the LPSIL+GE group vs. C+GE (p<0.05). The renal CL(ge) was less (2.2±0.59 vs. 3.8±0.53 mL/min·kg(-1), p<0.05), while the total CL(ge) was comparable (5.9±1.5 vs. 6.7±1.1 mL/min·kg(-1); p=0.30). In the LPSIL+GE group relative to C+GE, the half-life (t(1/2)) was 79% higher (p<0.05) and GE concentrations detected at the end of the study in the plasma and kidney were elevated 2.5-fold (p=0.09) and 2.2-fold (p<0.05), respectively. The model reproduced several consequences of early sepsis like in patients such as capillary leak, a decreased glomerular filtration rate (GFR) and the changes in pharmacokinetics of GE (increased values of V(c) and t(1/2) and a drop in renal CL(ge) proportional to that of CL(cr)). Nonrenal routes which, for the most part, compensate the reduced renal CL(ge) in septic rats deserve further study.
Keywords: gentamiciny; lipopolysacharidy; kapilární permeabilita; Sepsis; interleukin-2; ledviny; Glomerular Filtration Rate; Lipopolysaccharides; sepse; Kidney; krysa rodu Rattus; antibakteriální látky; zvířata; Gentamicins; Capillary Permeability; hodnoty glomerulární filtrace; potkani Wistar; Interleukin-2; Rats, Wistar; Anti-Bacterial Agents; Male; Rats; Animals; mužské pohlaví; Disease Models, Animal; modely nemocí na zvířatech